Impact of metabolic dysfunction-associated steatotic liver disease on hepatocellular carcinoma risk in autoimmune hepatitis - Jihye Lim; Ye-Jee Kim; Sehee Kim; Ju Hyun Shim (PLoS ONE, 2025)
Few large-scale studies have investigated factors associated with the development of hepatocellular carcinoma (HCC) in patients with autoimmune hepatitis (AIH). This study aimed to determine the risk of HCC in AIH patients and associated risk factors, focusing on metabolic dysfunction-associated steatotic liver disease (MASLD). We analyzed the claims data from the Korean National Health Insurance Service from 2007 to 2020. The study included 7,382 patients with AIH and a control group of 58,538 age- and sex-matched individuals, at a ratio of 1:8. We compared the incidence rates of HCC between these groups and investigated the risk factors of HCC. During a median follow-up of 5.9 years, 160 AIH patients were diagnosed with HCC, resulting in an incidence rate of 3.60 per 1,000 person-years. The matched controls exhibited an incidence rate of 0.48 per 1,000 person-years. After adjustment, AIH patients had a 4.85-fold heightened risk of HCC compared to the control group. Within the AIH cohort, the presence of coexisting MASLD further elevated the risk of HCC, along with other factors such as older age, male sex, and decompensated liver cirrhosis, as observed in a two-year landmark analysis. The presence of concurrent extrahepatic autoimmune diseases did not affect the prognosis, while glucocorticoid treatment was associated with a decreased risk of HCC. Patients with AIH had an increased risk of HCC compared to matched controls, particularly those with coexisting MASLD. In addition to appropriate medical treatment, proactive interventions and lifestyle modifications for concurrent MASLD are recommended for these patients.